Health in industry - Mackenzie, James; Haldane, William S.
1927-02-25 1927 1920s 4 pages Workers’ Appreciation. 1925 was the first year of this actual work, then confined to Scotland. Thanks to the enthusiasm of their secretary, Mr. Mackenzie, meetings of workers were organised throughout Scotland, mainly in the mining and industrial areas, to the number of between 70 and 80. In that initial effort they had from the start splendid help from the medical profession, for the doctors and medical officers, particularly those in the industrial districts, recognised at once the value of the work undertaken, and readily gave their aid. But what had more than anything encouraged them was the wonderful appreciation of the workers themselves. The workers’ own organisations were quick to grasp the position, and their leaders gave wide-minded assistance and encouragement in making effective throughout the industrial communities work which it would have been difficult to organise without their strong leading and support. The success of their efforts in Scotland soon became known in the North of England, and before the end of 1925 a call reached them to extend their work across the Border. Sir Thomas Oliver, of Newcastle-on-Tyne, had given them invaluable help with his unsurpassed knowledge of the subject of occupational diseases and his world-wide repute. Largely due to his interest and standing, the English demand took forcible shape, and they could not resist it. Last year they resolved that England must be included in the scope of their effort. For that purpose it became necessary to re-organise themselves as a Society, with Area Councils and local organisations throughout Great Britain. The new constitution was adopted in October last, and five Area Councils formed covering the whole country. It was instructive of the success and acceptance of their efforts that while last year their work increased 50 per cent. on that in 1925 in the number of meetings, addresses and talks arranged, in the first three months of this year they had already fixed engagements 50 per cent. more than those for the whole of last year, and for the whole of 1927 he was confident they would more than double the work done. England and Scotland were now on a par in the work they were engaged on. He welcomed Sir Thomas Oliver and Dr. Clark Trotter, who had already done important work for the Society in London. Was it not significant that Sir Thomas Oliver in the North of England and Dr. Clark Trotter in the South were both Scotsmen by birth? (Applause.) 292/840/1/8